Corrigendum - Board, Editorial (Medical Word, 2026)
Corrigendum In the Journal Medical Word, Vol. 2(2), No 2, 2021, in the article in Section Current Topic: Krzysztof Filipiak, Nadjib Bouayed Pragmatism and Smoking Cessation: The Role of Harm Reduction in Creating Healthier Smoke-Free Societies Medical Word, Vol. 2(2), No 2, 2021, pp. 76-80 http://media.medicinskarec.com/2022/03/rad_076_080web-1.pdf in online and printed version of article important Note was omitted. The Editor-in-Chief has decided to publish a Corrigendum (Note) for this article. Corrigendum (Omitted Note): Note: This article is adapted from the original work titled “Pragmatism and Smoking Cessation: The Role of Harm Reduction in Creating Healthier Smoke-Free Societies” by Amanda Barrell (Brighton, UK), featuring interviews with Krzysztof Filipiak and Nadjib Bouayed. The original article is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License (https://creativecommons.org/licenses/by-nc/4.0/). This adaptation has been made for non-commercial purposes and includes modifications for clarity, structure, and updated context.